2019
DOI: 10.1002/adom.201900620
|View full text |Cite
|
Sign up to set email alerts
|

Highly Luminescent Gold Nanocluster Frameworks

Abstract: cytotoxic and are restricted in their use in nanomedicine. [6] Organic dyes, on the other hand, suffer from toxicity and poor photostability. [7] Therefore, the large potential of appropriate luminophores in biomedical applications has prompted intensive efforts toward the development of alternative nanomaterials with reduced toxicity and increased biocompatibility. A promising new approach is to exploit the photoluminescence of noble metal nanoclusters (NCs), having emissions in visible or near-IR regions, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 46 publications
3
58
0
Order By: Relevance
“…The Au4f7/2 XPS spectrum of CNC‐Au@GSH confirmed typical peak positions of gold nanoclusters with Au(0) core and Au(I) surfaces at 83.9 and 84.8 eV, respectively (Figure S3c, Supporting Information). [ 79 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Au4f7/2 XPS spectrum of CNC‐Au@GSH confirmed typical peak positions of gold nanoclusters with Au(0) core and Au(I) surfaces at 83.9 and 84.8 eV, respectively (Figure S3c, Supporting Information). [ 79 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 67–73 ] Among AuNCs, bovine serum albumin (BSA) coated gold nanoclusters (Au@BSA) and reduced glutathione (GSH) capped gold nanoclusters (Au@GSH) have been explored for sensors, catalysis, bioimaging, and pathogen detection. [ 74–86 ] However, their potential in biopolymer‐based composite fibers for optical amplification and waveguiding is unexplored to date.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are challenges because the number of luminescent gold NCs is limited and the PL quantum yield is low compared to organic dyes, lanthanide complexes and SCQD-based nanomaterials. To improve the quantum yield and PL, various approaches have been developed including ligand engineering, selective doping to create alloy clusters, aggregation-induced emission, selective etching and self-assembly [48][49][50][51][52][53][54][55][56][57][58].…”
Section: Review Luminescent Gold Nanoclustersmentioning
confidence: 99%
“…The NC assemblies have been used to encapsu- late poorly water-soluble fluorinated drugs through nanoconfinement [97]. Chandra et al recently reported highly luminescent gold nanocluster frameworks (AuNCFs) using selfassembly through metal chelation [53]. Glutathione-capped AuNCs [Au 25 (SG) 18 ] spontaneously self-assembled into spherical AuNCFs upon controlled addition of SnCl 2 ( Figure 6C).…”
Section: Imaging and Labeling Mammalian Cell Linesmentioning
confidence: 99%
“…reported the fabrication of highly luminescent Au NC frameworks (GNCFs) by coordinating divalent cations with carboxylate anions present on the NC surface. [ 319 ] [Au@SG] NCs were prepared by heating the presynthesized Au‐thiolates at 70 °C for 24 h. Surprisingly, the addition of Sn 2+ ions into the above prepared NCs has shown a seven‐fold enhancement in their PL due to the coordination‐assisted assembly. Interaction of negatively charged carboxylate group of SG with divalent Sn 2+ cations resulted in the formation of GNCFs via inter‐NC crosslinking, which was confirmed by observing 3D spherical colloidal structures in STEM and ET ( Figure ).…”
Section: Molecular Interactions In Nc Self‐assemblymentioning
confidence: 99%